SOIL-STRUCTURE INTERACTION ANALYSES OF PILE SUPPORTED BUILDING FRAME - H.S. Chore; R.K. Ingle (ASEAN Journal on Science and Technology for Development, 2008)
The effect of the soil-structure interaction on the simple single storeyed and two bayed space frame resting on pile group of two piles with flexible cap is examined in this paper by resorting to more rational approach and realistic assumptions. Initially, 3-D FEA is carried out independently for the frame on the premised of fixed column bases. Later, pile foundation is worked out separately. The stiffness so obtained for foundation is used in the interactive analysis of frame to quantify the effect of soil- structure interaction on the response of the superstructure. For modeling the foundation system two approaches of finite element analysis are used. In the first approach complete three dimensional finite element analysis is resorted to wherein pile, pile cap along with the soil are discretized into 20 noded isoparametric continnum elements and interface between pile and soil is idealized as  6 noded isoparametric interface elements. In the second approach simplified finite element analysis procedure is used wherein beam element, plate element and spring elements are used to model pile, pile cap and soil respectively.  The salient feature of the investigation is that the interaction between pile cap and soil underlying it is considered. In the parametric study presented here, effect of pile spacing and pile configuration is evaluated on the response of superstructure in the form top displacement in frame and bending moment at top as well as bottom of the superstructure columns. Results obtained by either analysis are compared.